Assessing Efficiency for the Beef Cow - Travis D. Maddock; G. Cliff Lamb (EDIS)
AN231, a 4-page illustrated fact sheet by Travis D. Maddock and G. Cliff Lamb, helps beef producers better understand what drives efficiency for the beef breeding herd. Includes references. Published by the UF Department of Animal Sciences, February 2010.